Religious leadership for family planning - Rafiq, Mohamed Yunus, author. aut Link Link Link
1 online resource.
Keywords: "Over the last thirty years, religious leaders in Tanzania have increasingly been recruited to participate in sensitive health programs like family planning. This book considers what happens when religious leaders, often envisaged as central to a project's success, are unavailable. Based on extensive ethnographic research, the book argues that in those situations, public health NGOs often create and co-opt religious leaders from religiously adjacent figures such as healers, marriage counsellors, and Quran teachers. These newly crafted religious leaders then in turn actively adapt and reshape their roles in ways that accommodate and sometimes diverge from the project's intentions. Challenging the conventional view of development as a linear process between developer and developee, this book reveals development as a layered and dynamic process shaped by intersecting visions and competing desires for spatio-temporal transformation. The book uses the Kiswahili concept kujiendeleza ('to make oneself go') to capture the awkward, unequal and creative connections between NGOs and the Muslim and Christian religious leaders they work with for the implementation of their plans. Far from being passive or disengaged, local actors actively engage with family planning and development projects in ways that reflect both their agency and the complexities of their socio-political contexts. Providing an innovative and nuanced theorization of development, religion, and health, this book will be an important read for researchers of African Studies, and of faith-based development"-- Provided by publisher.